Blockchain-based edge computing for medical data storage & processing using federated learning - Faiyaz, Fazle Rabbi; Lisa, Afrin Sultana; Rahat, Laisa; Tabassum, Nafisa; Istiaq, Walid Bin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.